General equilibrium trade policy analysis with structural gravity - Mario Larch; Yoto V. Yotov (World Trade Organization (WTO), 2016)
The objective of this manuscript is to serve as a practical guide for evaluation of the general equilibrium (GE) effects of trade policy using the structural gravity model. We try to achieve this objective in four steps. First, we focus on the original Armington CES gravity model, as a representative framework for a large class of GE models, to offer a deep analysis of the structural relationships underlying the general equilibrium gravity system, and how they can be exploited to make trade policy inferences. Second, we present and discuss a series of indexes that can be used to summarize the GE effects of trade policy. Third, we summarize the standard procedures to perform counterfactual analysis with the gravity model, and we outline recent methods to obtain theory-consistent GE effects of trade policy with a simple estimation procedure that can be performed in any statistical software package capable of estimating a poisson model (e.g. Stata). Finally, we demonstrate how gravity can be integrated with a broader class of general equilibrium models by nesting the Armington-CES model within a dynamic production superstructure with capital accumulation.
Keywords: F13; F14; F16; 330; Structural Gravity; Trade Policy; General Equilibrium Analysis